Development of Student Worksheets Electronic (E-LKPD) for Geometry Transformation Materials - NOR CHOFIFAH; Atik Wintarti (MATHEdunesa, 2023)
The purpose of this study is to develop an e-LKPD using a Live Worksheets with GeoGebra-assisted for geometric transformations, especially translation. The translation sub-topic was chosen because many students still need help finding translation concept. The type of research carried out in development research to produce e-LKPD using the ADDIE method consists of stages Analysis, Design, Development, Implementation, and Evaluation. The test subjects in this study were 15 students with high, medium, and low math ability categories. Subjects are divided into three categories to determine students' understanding of the e-LKPD so that they are able to achieve learning mastery. Students from junior high school (SMP Negeri 39 Surabaya) were selected as subjects because they had never used GeoGebra-assisted e-LKPD. The data collection instruments in the study consisted of validation sheets, learning outcomes tests (THB) and student response questionnaires. The results of this study indicate that the validation results with an average score of 3.73, which means that the e-LKPD on translation is included in the very valid criteria and is feasible to use. The analysis of the use of e-LKPD shows that the average student response is 3.39, which means e-LKPD is positive and practical. Based on the test scores for learning outcomes, 14 of the 15 research subjects scored pass the KKM, so using e-LKPD can help students learn about translation materials. Thus the translational e-LKPD using a GeoGebra-assisted Live Worksheets are valid, practical and effective. Keywords: e-LKPD, Geometry Transformation, Translation, Geogebra, Live Worksheets.